Nondestructive evaluation of welded joints using digital image correlation - Eshteyah, Mohanna; Hijazi, Ala; Hrairi, Meftah; , (Springer, 2015)
This paper demonstrates a novel approach in which the digital image correlation technique is used as a nondestructive testing tool for the inspection of welded joints. In this approach, the joint is loaded with the maximum load that it is expected to encounter during actual operation (i.e., the design load) and two images are recorded, one before and one after applying the load. Artificially made defects of different types and sizes were introduced along the welding line of a butt-welded joint. The results of this study show that this approach can be used for detecting different types of welding defects; however, it cannot distinguish between the different types of defects. The results also show that the minimum detectable defect size depends on the type of the defect. The minimum detectable defect size using this approach was found to be smaller than the maximum acceptable defect length according to the American Petroleum Institute acceptance criteria for most of the defect types investigated here. Also, results of a selected group of samples are compared to the results obtained using the well-established and widely used radiographic imaging technique, for reference purposes.